Answer: ...
To solve the first part Let us assume a expression (E) that contains rational exponents:
E = 6² / ( 9 × 3 )
E = 6² / ( (3²) × 3 )
E = 6² / ( 3 × 3 )
E = 6² / 3
E = 6² / 3³
E = 36/27 = 4/3
E = 4/3
To solve the second part Let us assume a expression (F) that contains radicals:
F = 10 × √(∛(59 +5))
F = 10 × √(∛64)
F = 10 × √(∛(4×4×4))
F = 10 × √4
F = 10 × √(2×2)
F = 10 × 2
F = 20
Thus we have simplified the expression that contains rational exponents and also the expression that contains radicals also.
I hope you understood and liked my explanation.